2018
DOI: 10.29252/jhsme.5.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Islamic-based Spiritual-religious Psychotherapy on Components of Health-oriented Lifestyle in Female University Students

Abstract: Background and Objectives: Nowadays health-oriented lifestyle is the best way for prevention and having a healthy lifearound the world. Therefore it is necessary to identify and strengthen the factors that improve lifestyle. As a result, this study aimed to evaluate the effect of Islamic instructional-based spiritual-religious psychotherapy on health-oriented lifestyle in female students of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Based on the results of this study, when female children of divorced parents were exposed to spiritual-religious doctrines, they were able to cope with parental divorce and its problems in a better way. In line with this research, Athari et al in their study showed that spiritual and religious interventions can change one's lifestyle and make them adopt a healthier one (31). According to the findings of another study conducted by Simoni et al, spirituality and religion can help people adapt themselves to the difficulties in their lives and their incurable diseases (32).…”
Section: Discussionmentioning
confidence: 83%
“…Based on the results of this study, when female children of divorced parents were exposed to spiritual-religious doctrines, they were able to cope with parental divorce and its problems in a better way. In line with this research, Athari et al in their study showed that spiritual and religious interventions can change one's lifestyle and make them adopt a healthier one (31). According to the findings of another study conducted by Simoni et al, spirituality and religion can help people adapt themselves to the difficulties in their lives and their incurable diseases (32).…”
Section: Discussionmentioning
confidence: 83%
“…It seems that spirituality and religion may relieve distress by proposing positive approaches and attitudes. Athari et al indicated that spiritual-religious interventions can change lifestyle in girls by providing attitudes and lead them to adopt positive and productive behaviors (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they stated that spiritual-religious interventions can even result in posttraumatic growth (16). It has been shown in the literature that spiritual-religious interventions can strongly enhance emotional disturbance (17,18) and even attenuate the symptoms of schizophrenia disorder (19). Athari et al demonstrated that spiritualreligious interventions may impose a positive influence on people's lives and improve the self-actualization and health behaviors (20).…”
mentioning
confidence: 99%